The Hebrew Bible : Feminist and Intersectional Perspectives - Yee, Gale A., 1949- (Book collections on Project MUSE., 2018)
This volume provides an introduction and essays on the four key sections of the Hebrew Scriptures from the perspective of top feminist biblical scholars: Part One: Torah/Pentateuch; Part Two: Deuteronomistic History (Joshua 2 Kings); Part Three: Prophets and Prophecy; Part Four: Writings and the Book of Daniel. This volume highlights key issues in the Hebrew Scriptures from the perspective of top feminist biblical scholars. This includes historical critical and literary textual analysis and exegesis, particularly as viewed through feminist and intersectional interpretive lenses. Intersectional lenses include the racial/ethnic, class, Global South, postcolonial, and so forth, and their interconnections with gender. The introduction to the volume by the editor introduces feminist intersectional biblical scholarship, making the case that this scholarship addresses perspectives that are often missing from even very thorough survey texts: feminist and intersectional issues regarding the women characters, sexual assumptions, sexual and domestic violence, symbolization of women, class and race relations, and so forth. The essays have been created for students who may be encountering feminist biblical and intersectional scholarship for the first time.